2014
DOI: 10.1117/1.nph.1.1.011009
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse correlation spectroscopy for measurement of cerebral blood flow: future prospects

Abstract: Diffuse correlation spectroscopy (DCS) is an emerging optical modality used to measure cortical cerebral blood flow. This outlook presents a brief overview of the technology, summarizing the advantages and limitations of the method, and describing its recent applications to animal, adult, and infant cohorts. At last, the paper highlights future applications where DCS may play a pivotal role individualizing patient management and enhancing our understanding of neurovascular coupling, activation, and brain devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 60 publications
2
170
0
Order By: Relevance
“…In addition, the DCS blood flow index has been successfully validated against a plethora of gold-standard techniques [3,43]. Several recent reviews highlight the theory, implementation and applications of DCS [1,3,13,14,44], and therefore our background discussion will be brief.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the DCS blood flow index has been successfully validated against a plethora of gold-standard techniques [3,43]. Several recent reviews highlight the theory, implementation and applications of DCS [1,3,13,14,44], and therefore our background discussion will be brief.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
“…The most basic DOS/NIRS instrument measures diffuse reflectance from tissue as a function of input wavelength, and thereby derives the concentration of tissue chromophores and contrast agents, including oxyand deoxy-hemoglobin (HbO 2 , Hb), and changes thereof. Diffuse correlation spectroscopy (DCS), by contrast, is a more recently developed optical technique that utilizes the temporal intensity fluctuations of multiply scattered light in order to quantify microvascular blood flow in highly scattering tissues [13][14][15]. Like DOS/NIRS, the DCS method is non-invasive and penetrates tissue deeply, but DCS also offers the possibility to directly measure the "blood flow" contribution to tissue hemodynamics, continuously and at the bedside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] In traditional DCS analysis, the optical properties of the medium, absorption (μ a ), and reduced scattering (μ 0 s ) coefficients should be known and the errors in the estimation of these parameters influence the calculated blood flow index (BFI). Most significant errors come from errors in estimating the scattering coefficient, whereas the results are less sensitive to the absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Buckley et al [26][27][28][29] reported results obtained with a new optical method for determination of cerebral oxygen metabolism and regional cerebral blood using near infrared light. The measurements are based on diffuse optical spectroscopy (DOS) for quantification of cerebral tissue oxygen saturation and diffuse correlation spectroscopy (DCS) for monitoring cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%